The Effect Of Individual Taxpayer Compliance On Article 21 Income Tax Revenue At The Regional Office Of The Directorate General Of Taxes Of North Sumatra I - Meilinda Stefani Harefa; Eirene Nathasya Sitindaon (Publikasi Indonesia, 2023)
Indonesia is a developing country with a state goal, namely, to increase the country's development. To realize growth, funds are needed, which come from relatively significant state revenues. The state revenue that makes the most significant contribution is tax sector revenue. Taxes are people's contributions to the state treasury based on law, which can be imposed without receiving direct reciprocal services and are used for general expenses. So, action is needed to increase tax revenues. This research aims to determine the effect of individual taxpayer compliance on income tax revenues under Article 21. The data collection techniques used in this research are documentation and questionnaires. The population in this study was 1,695,904 individual taxpayers registered at the Regional Office of the Directorate General of North Sumatra I. The sampling technique in this research is Non-Probability Sampling, namely Random Sampling using the Slovin formula. The data analysis technique used is a descriptive statistical analysis using SmartPLS-based Partial Least Square (PLS) software. This research indicates that Individual Taxpayer Compliance has a positive and significant effect on Income Tax Revenue Article 21 at the Regional Office of the Directorate General of Taxes, North Sumatra I.